055 Medidraw: development of a mobile application (App) to capture and quantify freehand medical drawing. (December 2018) - Egawa, M; Abdulraze, G; Choi, K; Mohamedally, D; Cross, M; Sebire, NJ
Abstract : Background: Medical drawings form an important part of the patient record, but currently, most are paper-based freehand drawings with associated problems with storage and subjective assessment. The aim of this study was to create a cross-platform medical drawing application (app) that represents data in a standardised, quantifiable, digital format with efficient storage and retrieval. Methods: We developed a cross-platform web-based application using node.js, Heroku, JSON and AJAX backend combined with an HTML, HTML Canvas, javascript and CSS front end. Results: We demonstrate a working prototype of the Medidraw web app which allows freehand capture and drawing on standard templates of features such as lacerations and bruising, with automated quantification and separation of body areas. The app provides additional functionality compared to existing medical digital drawing apps such as the provision of quantitative information and further customisation will enable rapid, real-time quantification and linkage to individual records. Conclusion: Further work is required to extend the functionality to all body sites, to increase the range of templates available and to develop a SMART on FHIR interface for seamless integration with an electronic patient record system.